Pendidikan Multikultural Berbasis Afektif Sufistik bagi Pembentukan Karakter - Pariyati Pariyati (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
AbstractThe concept of Islamic religious education such as kalam and fiqih is more directed towards the development of affective capable of experiencing multicultural realities, so that the spirit of Sufi teachings that develop multicultural morality through two things: the first